(3GdeMUhd aj TQM GdaUhds - (3CHh GdMSf LeGd GdOjf MSjf Hf HOQ Hf EHGR Hf YHO Gddg GdfMhis; (3GHf eYWj , jMji Hf YHO GdeYWj Hf YHO GdfhQ GdRhGhj, Rjf GdOjf CHh GdMSjf,J (B628 (3g` s ((3eMeO Hf SYjO Hf YHO GdSdGe GdUfgGLi GdeQGcTi s)
(3ChdgG (B:s
(3GdMeO ddg hHYO , aGf cJGH GdaUhd ai GdfMh ddTjN GdEeGe Hf eYWi hGf cGf TOjO GdGNJUGQ YGQjkG ef GdJWhjd hGdEcKGQ s
(3BNQgG (B:s
(3adeG GdJbJ GddGeGf hJYPQ GdGOZGe HSchf GdGe GdKGfjI MPaJ GdChdi JNajakG (B, (3hgfG dbWY GdcdGe ai gPG GdTQM QGLjkG ef Gddg YR GSeg Cfg jfaY Hg hGdMeO ddg ced GdcJGH s
(3GdfSNI HgG MhGTs
(3HChdg agQSs
(3HgG fXGe GdJYbjHIs
(3aQZ ef JCdjag SfI (B674 s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdfMhs